PENDIDIKAN IBU DAN DUKUNGAN SOSIAL TERHADAP PEMILIHAN KB PASCA PERSALINAN - Sakti, Ina Rahayu; Kusuma, Inggar Ratna (Jurnal Keperawatan dan Kesehatan, 2025)
Postpartum contraceptive method selection remains a critical issue in reproductive health, significantly impacting unplanned pregnancy rates and maternal-child well-being. This study aimed to analyze the relationship between maternal education level and social support with postpartum contraceptive use (PPCU) in Indonesia. Employing a quantitative cross-sectional design, data were collected from 252 purposively sampled respondents and analyzed using chi-square tests via SPSS. Results demonstrated significant associations between education level and PPCU (p=0.012) and between social support and PPCU (p=0.014). Mothers with higher education were more likely to choose effective contraceptive methods. Additionally, strong social support—particularly from spouses, family, and healthcare providers—was shown to enhance maternal participation in PPCU programs. The findings underscore the importance of education and social environment in influencing postpartum contraceptive decisions. Consequently, interventions focusing on knowledge-based health education and strengthening family support systems are crucial to improving the uptake and success of postpartum family planning initiatives in Indonesia.